O projeto "Arenito Nova Fronteira" e o avanço das lavouras temporárias nas terras de pasto - Fonseca, Fernanda Perdigão da (2006)
The northeastern region of Parana had its first economical use directed to coffee husbandry, such activity being predominant until the 70's in practically all the northern portion of the state. After this period, the growing of coffee suffered a crisis which gradually led into the development of pasture for cattle. Such activity, based on traditional methods with little or no chemical fertilization, lack of corrections and other cultural treatments, provoked the exhaustion of the soils characteristically more "fragile" and susceptible to erosive processes due to their geological structure: they are soils originated from the arenitic groundings of the Caiuá Formation. With this regional picture in mind, as for the environmental aspects as well as for, consequently, the social economical aspects, from 1997, the "Projeto Arenito Nova Fronteira" (New Frontier Arenit Project) comes to scene. Captained by Cocamar (Agroindustrial Co-operative of Maringa), it brings the proposal to reinvigorate the economical and ecological conditions of the micro region of Umuarama, mainly through the system of renting land associated with the husbandry (crops and cattle integration) process. Therefore, this research aims at analyzing the main impacts verified in the northeastern region of Parana, and, specially, in the restricted area of study, from the implantation of the "Projeto Arenito Nova Fronteira".